The effect of implementation of asset management and competence of state apparatus - Cahaya Azwari, Peny; Nur Affiah, Nunuy; Yadiati, Winwin; Fitrijanti, Tettet (Opción, 2019)
This research aims to verify the effect of the implementation of asset management and the competence of the state civil apparatus on the financial reporting quality by using multiple regression analysis as a method. The results show that the implementation of asset management and competence of the state apparatus of each state gave positive and significant influence on the financial reporting quality. In conclusion, the components or dimensions of knowledge, skills, and abilities indicate that the competence of the state apparatus exerts a large influence on the financial reporting quality.